Analisa Kebutuhan Bahan Bakar Gas LPG Untuk Insinerator Limbah Medis Dual Chamber Oxy-Fuel Dengan Variasi Laju Volume Air Yang Diinjeksikan - Pasek Purnama, I Made; Suprapta Winaya, I Nyoman; Arya Darma, I Wayan; Angga Yuda Pratama, I Putu (Teknik Desain Mekanika; Vol 12 No 4 (2023): Oktober 2023 : Teknik Desain Mekanika, 2023)
Abstractt This study aims to evaluate the consumption of LPG gas fuel in an oxy-fuel dual chamber incinerator with variations in the injected water flow rate. Each sample of medical waste weighing 1 kg was used in the experiments. The incineration process was carried out at a primary chamber temperature of 800°C and a secondary chamber temperature of 1000°C, with a burning duration of 3 minutes. Four different water flow rates were tested: 20 ml/minute, 30 ml/minute, 40 ml/minute, and 50 ml/minute. In each variation, an oxy-fuel injection rate of 8 l/minute was used. Careful adjustment of the water flow rate is crucial as excessive water addition can disrupt the burner's performance. By optimizing this adjustment, the industry can achieve the best efficiency and performance in medical waste treatment while reducing the environmental impact. Keywords: Dual Chamber Incinerator, Gas Fuel Consumption, Volume Flow Rate, Medical Waste, Medical Waste Treatment, Oxy-Fuel Injection.